2015
DOI: 10.1002/ca.22632
|View full text |Cite
|
Sign up to set email alerts
|

The effects of body mass index and age on cross‐sectional properties of the femoral neck

Abstract: Research on the relationship between body mass index (BMI) and cross-sectional geometry of long bone diaphyses demonstrates that strength properties are significantly greater in obese versus normal BMI individuals. However, articular dimensions do not differ appreciably. If femoral head size remains constant, we hypothesize that the femoral neck remodels to accommodate greater loads associated with increased BMI. High-resolution CT scans (n = 170 males) were divided into three BMI groups (normal, overweight, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Wheeler et al, 8 in their study of the cross-sectional geometry of long bone diaphyses that correlated BMD, BMI, and age, demonstrated that bone strength is significantly higher in obese individuals when compared with those with normal BMI. However, the joint dimensions do not differ appreciably; older individuals with a higher BMI are less likely to develop a fracture than younger individuals with normal BMI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wheeler et al, 8 in their study of the cross-sectional geometry of long bone diaphyses that correlated BMD, BMI, and age, demonstrated that bone strength is significantly higher in obese individuals when compared with those with normal BMI. However, the joint dimensions do not differ appreciably; older individuals with a higher BMI are less likely to develop a fracture than younger individuals with normal BMI.…”
Section: Discussionmentioning
confidence: 99%
“…The specialized literature emphasizes that bone mineral density (BMD), an age-related predictor of fracture, is not always consistent: individuals with very low femoral neck BMD may not present fracture, while those with normal BMD might. 8 There may be other relevant variables that determine fractures and especially their types, such as bone anatomy. 8 , 9 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However this study did not consider the effect of obese BMI on bone cross sectional area (CSA), geometry, and material properties. Recent studies have shown that BMI and age can have a direct effect on bone CSA, geometry, and material properties …”
Section: Methodsmentioning
confidence: 99%
“…On the one hand, obese people have chronic inflammation that predisposes bone osteolysis, which leads to the development of osteoporosis [10]. On the other hand, increased body mass, and hence greater load on the hip joint may have a positive effect on the femoral neck [12]. Our study did not check the effect of body mass on bone density and structure, only on its thickness.…”
Section: Discussionmentioning
confidence: 83%